MCM-41-supported ruthenium carbonyl cluster-derived catalysts for asymmetric hydrogenation reactions - Indra, Arindam; Basu, Susmit; Kulkarni, Dhanashree G.; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Applied Catalysis A-General, 2008)
{The anionic ruthenium carbonyl cluster [Ru-4(mu-H)(3)(CO)(12)](-) has been ion-paired with (3-chloropropyl)-trimethoxysilyl-cinchonidium or sparteinium groups chemically bound to the surfaces of MCM-41 [(MCM-41-)(-O)(3)SiCH2CH2CH2NR3+Cl-
Keywords: asymmetric catalysis; functionalized MCM-41; hydrogenation catalysts; nanocatalyst; ruthenium carbonyl cluster

Template free synthesis of mesoporous TiO2 with high wall thickness and nanocrystalline framework - Kulkarni, Dhanashree G.; Murugan, A. Vadivel; Viswanath, Annamraju Kasi; Gopinath, Chinnakonda S. (Journal of Nanoscience and Nanotechnology, 2009)
A simple procedure to prepare nanocrystalline mesoporous titania (meso-TiO2) is reported without any templating agent and it possesses a high BET surface area and a large pore wall thickness (11.3 nm) than that of meso-TiO2 prepared by other methods. Nanocrystalline meso-TiO2 also has been synthesized with hexadecylamine template for comparison through known procedure. The meso-TiO2 materials were characterized by X-ray diffraction, FT-IR, UV-Vis absorbance spectra, thermal analysis, SEM, HRTEM and textural properties through N-2 adsorption-desorption isotherms. Spherical shape particles in a range of few hundred nanometers are obtained in the template free method. Above systematic characterization provides direct indications toward the mechanism of formation of meso-TiO2 in the template free method. A comparison of the physical and textural properties indicates a possibility of coarse-tuning of the textural characteristics of mesoporous TiO2 by adopting different preparation methods.
Keywords: Mesopore; Mesopore Formation; Template-Free; Thick Wall; titania